A Review on Energy Policies and Scenario in India - Shweta Goyal; Sachin Mishra; Anamika Bhatia (Institute of Advanced Engineering and Science, 2017)
Now a day’s Energy plays a vital role in every sector like agriculture, industry, transport, commercial and domestic. Energy is the primary key for development of the country. Only two types are sources for energy generations are presents that are Non Renewable and Renewable Sources. But due to climate change and fossil fuel depletion renewable sources are becoming major reason for focusing for energy generation. Renewable Energy (RE) generation is useful to decrease pollution, global warming etc. Although the high cost of the renewable energy generation is the main barrier in this field but there are many schemes which plays a very important role in this field. These policies encourage the consumer to used renewable sources for energy. This paper introduces the main energy challenges in India and different types of energy policies existing to overcome that challenges. What the institutional programs presenting in India for energy policies are.